Sistematización de la práctica profesional 1 y 2, desarrollo de una metodología de enseñanza para la danza del torbellino cundinamarqués en Adulto Mayor de la Casa de Cultura de Mosquera Cundinamarca durante el periodo 2022-2 y 2023-1 - Lara Pedraza, Ingrid Johanna (Universidad Antonio Nariño, 2024)
The research project "Systematization of Professional Practice 1 and 2: development of a Teaching Methodology for the Cundinamarqués Whirlwind Dance in Older Adults of the Mosquera Culture House, Cundinamarca (2022-2 and 2023-1)" has as main objective the systematization of pedagogical experiences 1 and 2 carried out with the group of Seniors of the Mosquera House of Culture, this project focuses on the systematization and development of a teaching methodology for the Cundinamarca Whirlwind Dance, directed to older adults at the Mosquera Culture House, with the purpose of improving their physical and motor skills and quality of life, while investigating the emotions and expressions that arise during the practice.